Concussion-prevention strategies used in National Collegiate Athletic Association Divisions I and II women's soccer - Jeffries, K. K.; Girouard, T. J.; Tandy, R. D.; Radzak, K. N. (Journal of Athletic Training, 2020)
Context: Whereas much attention has been paid to identifying mechanisms for decreasing concussion rates in women's soccer players, which strategies are currently being used is unknown. In addition, athletic trainers' (ATs') knowledge and beliefs about the efficacy of concussion-prevention practices have not been studied. Objectives: To evaluate the concussion-prevention strategies being used in National Collegiate Athletic Association Division I and Division II women's soccer and identify the beliefs of certified ATs regarding mechanisms for preventing concussion. Design: Cross-sectional study. Setting: Online survey. Patients or Other Participants: A total of 223 women's soccer team ATs employed at Division I or II universities. Main Outcome Measure(s): A survey instrument of structured questions and open-ended, follow-up questions was developed to identify the use of cervical-strengthening programs, headgear, and other techniques for preventing concussion. Questions also addressed ATs' beliefs regarding the effectiveness of cervical strengthening, headgear, and mouthguards in concussion prevention. Data were collected via questionnaire in Qualtrics survey software. Descriptive statistics of frequencies and percentages were calculated for close-ended questions. Open-ended questions were evaluated for common themes, which were then reported by response frequency. Results: Cervical strengthening or stability for concussion prevention was reported by 38 (17.12%) respondents; 153 (69.86%) ATs believed that cervical strengthening would aid in concussion prevention. Seventy-eight (35.49%) reported that their players wore headgear. Nineteen (8.76%) believed that soccer headgear prevented concussions; 45 (20.74%) believed that mouthguards prevented concussions. Education in proper soccer technique was reported by 151 (69.59%) respondents. Fourteen (0.06%) respondents cited nutritional strategies for concussion prevention. Conclusions: Although ATs believed that cervical strengthening could help prevent concussions, few had implemented this strategy. However, the ATs whose teams used headgear outnumbered those who believed that headgear was an effective prevention strategy. Based on our findings, we saw a disconnect among the current use of concussion-prevention strategies, ATs' beliefs, and the available evidence.